Sensory evaluation practices - Stone, Herbert (Food science and technology (Academic Press), 1992)
This Second Edition of Sensory Evaluation Practices provides the background and understanding necessary to make informed decisions about managing a sensory evaluation program, designing tests, and interpreting and reporting results. The authors have been in the sensory management consulting business for more than 20 years and bring their expertise to the enthusiastic and comprehensive revision of this invaluable book. Sensory evaluation of a product is the measurement of what is perceived about that product-not only in terms of its efficacy, but also by the more subtle influences of sight, smell, taste, touch, and where applicable, sound. A key benefit from this exciting and quantitative science is cost reduction in product reformulation due to the ability to evaluate a product's consumer acceptance in the marketplace.